Why Do Evangelicals Support Israel?. Issue 1 (March 2021) - Inbari, Motti; Bumin, Kirill M.; Byrd, M. Gordon
Abstract: This study considers the sources of evangelical support for Israel, utilizing an original survey of 1, 000 evangelical and born-again respondents. The results show that the three strongest predictors of evangelical and born-again Christian support for Israel are (1) age (older respondents are more supportive); (2) opinion of Jews; and (3) socialization (frequency of hearing other evangelicals talking about Israel). Our results also show that evangelical support for Israel is driven by respondents' beliefs rooted in evangelical Christian theology on eschatology and Biblical literalism. Thus, the most significant ideological statements that were found in the research were that the "State of Israel is proof of the fulfillment of prophesy regarding the nearing of Jesus' Second Coming" and that "Jews are God's chosen people." Another important finding is that there is less support toward Israel among young evangelicals (ages 18–29).